EVALUASI SISTEM DRAINASE POLDER KOTA SEMARANG DILIHAT DARI SUDUT PANDANG KOTA RAWAN BENCANA BANJIR - Marselly Dwiputri; Sarah Aisha; Rafi Mentari (RUSTIC, 2021)
One of the flood disasters that often hit Semarang City is caused by the lack of management of the drainage system which ultimately has great potential for the emergence of very adverse flood disasters. The condition of the drainage channel capacity that continues to decrease due to sedimentation, garbage, and poor maintenance also aggravates the flood problem in Semarang City. Flood management in Semarang City has been carried out with the development of polder system drainage in the Old City and Banger River areas of Semarang City. Based on these conditions, an analysis was carried out that aims to evaluate the concept of polder system drainage in Semarang City in solving flood problems. The method carried out in this study is to use a qualitative descriptive analysis of the flood resolution program through the polder system in Semarang City. The results of the analysis explained that the polder system had been built in accordance with existing principles and regulations but the lack of maintenance of the Polder Banger resulted in the polder function not being optimal. The concept of developing Banger polders in East Semarang was well developed based on considerations of safety, sustainability, and flexibility aspects.